Biosolids-derived phosphorus persists in Florida sandy soils - JoAnn B. Donald; Robert G. Hatfield; Rex Ellis; Todd Z. Osborne; Allan R. Bacon; Yang Lin (Geoderma Regional, 2025)

Spatiotemporal Patterns in the Biomass of Drift Macroalgae in the Indian River Lagoon, Florida, United States - Lauren M. Hall; Lori J. Morris; Robert H. Chamberlain; M. Dennis Hanisak; Robert W. Virnstein; Richard Paperno; Bernhard Riegl; L. Rex Ellis; Ali Simpson; Charles A. Jacoby (Frontiers in Marine Science, 2022)
Drift macroalgae plays key roles in the ecology of many coastal systems, including the Indian River Lagoon. In the lagoon, changes in the biomass of drift macroalgae may have interacted with an unprecedented bloom of phytoplankton in 2011. Patterns in the biomass of drift macroalgae were identified using new and original analyses of data from several sampling programs collected between 1997 and 2019. All available data show a relatively low biomass of drift macroalgae in 2010–2012, and surveys of fixed transects and seining as part of a fisheries independent monitoring program also recorded low biomass in 2016. Low light availability and potentially stressful temperatures appeared to be the main influences as indicated by the results of incubations in tanks to determine environmental tolerances and data on ambient conditions. Decreased biomass of drift macroalgae had implications for cycling of nutrients because carbon, nitrogen, and phosphorus not stored in the tissues of drift macroalgae became available for uptake by other primary producers, including phytoplankton. The estimated 14–18% increases in concentrations of these elements in the IRL could have promoted longer and more intense phytoplankton blooms, which would have reduced light availability and increased stress on algae and seagrasses. An improved understanding of such feedback and the ecological roles played by drift macroalgae will support more effective management of nutrient loads and the system by accounting for cycling of nutrients among primary producers.